Fraksi Heksan dan Fraksi Metanol Ekstrak Biji Pepaya Muda Menghambat Spermatogonia Mencit (Mus Musculus) Jantan - Satriyasa, Bagus Komang; I Pangkahila2, Wimpie (Jurnal Veteriner; Vol 11 No 1 (2010), 2010)
To avoid population booming, family planning program should be maintained in which menand woman have the same rights and obligations. However in execution of family planning the roleof men is still low. Studies about contraception in men are limited. Male contraception that isknown in society are condom and vasectomy. In the recent few years in particular, researcheshave been refocused on investigating traditional plants as anti fertility. In use researches manyplants have been studied, including papaya seed. Some researches on herbal anti fertility propertiesof papaya seed have been carried out including those on the active compounds of anti fertility, onapprolaki-lakite dosage of extract of carica papaya seed by animal experiments. Hexane fraction ofunripe papaya seed extract contains glycosides, alkaloid and triterpenoids, which is assumed hasan antifertility effect, so it can be used as a male contraceptive, although the mechanism of actionis not yet clear. Research is conducted at Animal Laboratory Unit Department of PharmacologyFaculty of Medicine University of Udayana, and Laboratorium Patologi Balai Penyidikan danPengujian Veterian (BPPV) Wilayah VI Denpasar Direktorat Jenderal Peternakan, DepartmentPertanian. This study used the pre-test and post-test control group design, using 30 male mice ofbalb C strain, aged 12 weeks, weight 20-22 gram, subsequently grouped by random into 3 groupseach consisting of 10 male mice. One control group (P0 = control group) was given double distilledwater, and two treatment groups (P1 = treatment group) was given fraction of the hexane extractof young Carica papaya seed 20 mg/20gram Body wieght/day, (P2 = treatment group) was givenfraction of the methanol extract of young Carica papaya seed 20 mg/20 gram/day). After 36 days oftreatment, evaluation of the testis, of the male mice was conducted. Data were analysed by normalitytest of Shapiro-will, homogeneity test, and Anova test. This study showed that cells of spermatogoniaA decreased significantly (p < 0,01). It is concluded that hexan fraction and methanol fraction ofunripe carica papaya seeds extract can decrease spermatogonia A cell of male mice (mus musculus).
Keywords: Fraction hexane extract of young Carica papaya seeds, fraction methanol extract of young Carica papaya seeds, spermatogonia A, male mice.